Genitourinary defects, anxiety and aggressive-like behavior and glucose metabolism disorders in Zmym2 mutant mice with inserted piggyBac transposon - Dai, Rufeng; Yin, Ye; Yu, Minghui; Zhang, Yumeng; Zhang, Jingjia; Liu, Tianyi; Fang, Xiaoyan; Wu, Xiaohui; Shen, Qian; Xu, Hong (Frontiers in Cell and Developmental Biology, 2025)
Mutations in ZMYM2 lead to syndromic congenital anomalies of the kidney and urinary tract (CAKUT) in humans. Tbx18 is co-expressed with Zmym2 in mesenchymal compartment of developing mouse ureter, indicating a potential in vivo relevance of the TBX18–ZMYM2 protein interaction in ureter development. The presence of multiple phenotypes beyond the urinary system in CAKUT patients carrying ZMYM2 mutations suggests that ZMYM2 has extensive roles in various developmental processes. This study aims to comprehensively examine the multi-phenotypic consequence of ZMYM2 mutations, with a particular focus on the roles of ZMYM2 in embryonic development, late metanephros formation, and the reproductive, nervous and endocrine systems, in addition to its role in urinary system. Using a new Zmym2 mutant mouse model with an inserted piggyBac transposon (PB), we found that homozygous Zmym2 mutations resulted in severe growth retardation of embryos by embryonic day 9.5 (E9.5D) and lethality from E10.5D. Heterozygous mutations caused morphogenetic issues in the genitourinary system, including duplex kidneys, vesicoureteral reflux (VUR), and cryptorchidism. And these heterozygous mutants exhibited anxiety and aggressive-like behaviors, and glucose metabolism disorders. Additionally, Zmym2 mutations induced duplicated ureteric bud (UB) eruption and abnormal nephrogenic zone extension, contributing to duplex kidney formation. Reduced apoptosis in the nephric duct might have contributed to abnormal ureter-bladder connections, which could explain the observed cases of VUR. Notably, Tbx18 is co-expressed with Zmym2 in mouse kidney, reduced Tbx18 expression in Zmym2 mutants further supports the hypothesis that Zmym2 interacts with Tbx18 during kidney development. Zmym2 PB mouse is the first model to demonstrate roles of Zmym2 in neuroethology and endocrinology, extending its significant beyond genitourinary defects and embryonic development. Further investigation of these phenotypes in CAKUT patients carrying ZMYM2 mutations will enhance our understanding of their phenotypes and improve strategies for early diagnosis, monitoring, and treatment.